A correlação entre cervicalgia, disfunção temporomandibular e ansiedade em acadêmicos de medicina - Mélo, Sandra Fernandes Pereira de (2023)
Abstract: Temporomandibular disorders (TMD) and cervical spine dysfunction encompass clinical problems of the musculoskeletal structures of the masticatory system and cervical spine. Clinical manifestations such as pain, joint noises and irregular or deviated mandibular function are frequent. The association between signs and symptoms of the muscles of the stomatognathic system and the cervical system or other areas is also common. The literature describes psycho-emotional factors, including anxiety, as causing or aggravating temporomandibular disorders, sometimes requiring treatment of these factors prior to joint treatment. The main objective of the research was to verify the correlation between neck pain, anxiety, and symptoms of temporomandibular dysfunction in medical students. The present research is characterized as a field study, with a descriptive character, where it will present a quantitative approach with the purpose of verifying the relationships between neck pain, anxiety, and symptoms of temporomandibular disorder in medical students. The sample consists of 119 students, who were selected through randomization, with an average of 15 students from the first to the eighth period of the undergraduate course. Three instruments were used for the research, the Neck Bournemouth Questionnaire (NBQ-Brazil), an instrument that has already been translated into Portuguese and validated, which aims at the presence of neck pain, the Diagnostic Criteria for Temporomandibular Disorders (DC/TMD), to identify signs and symptoms of temporomandibular disorders, in its summarized version. And the instrument in Portuguese of the State-Trait Anxiety Inventory (STAI). The mean age found was 24.55 years, with 58% of participants being female. The research pointed out that 37% of the participants have neck pain and 80.7% have symptoms related to TMD. Through the application of IDATE, it was observed that all students had some degree of anxiety, with the average degree having the highest incidence, with 59.6%. Despite the literature found massively correlating the three conditions, when an in-depth study was carried out through inferential statistics, using Pearson's Qi-square tests and the Spearman Test, the correlation between temporomandibular dysfunction, neck pain and anxiety was not presented, in the studied population.